KARAKTERISTIK DAN PERMASALAHAN UNTUK ANAK BERKEBUTUHAN KHUSUS - Nurwidyayanti Nurwidyayanti (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
Children with special needs (ABK) are children with special characteristics that are different from children in general without always showing mental, emotional or physical disabilities. Children with special needs are children who experience significant abnormalities/deviations (physical, mental-intellectual, social, and emotional) in their growth and development process compared to other children of the same age so that they require special education services. Children with Special Needs (ABK) is another term to replace the word "Extraordinary Children (ALB)" which indicates a special disorder. Children with special needs have different characteristics from one to another. Because of the characteristics and barriers they have, ABK requires a form of special education services that are tailored to their abilities and potential, for example for the blind they need to modify reading texts into Braille and the deaf communicate using sign language. Children with special needs usually attend special schools (SLB) according to their respective specialties. SLB section A for the blind, SLB section B for the hearing impaired, SLB section C for the mentally impaired, SLB section D for the quadriplegic, SLB section E for the hearing impaired and SLB section G for multiple disabilities. Every child with special needs has different characteristics from one to another, therefore it is important to carry out identification and assessment activities to identify their characteristics and needs.